1997
DOI: 10.1021/ef960088v
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Coal Direct Liquefaction by Steam Pretreatment

Abstract: Pretreatment of coal by reaction with subcritical steam enhances its performance in direct liquefaction. Illinois No. 6 coal, first reacted with 51 atm of steam for 15 min at 340 °C, was liquefied in a coal injection autoclave to provide rapid heating. Liquefactions were carried out with raw and pretreated coal at high-severity (400 °C, 30 min) and low-severity (385 °C, 15 min) conditions under 1500 psia of hydrogen with tetralin as the donor solvent. Substantial improvement in product liquid quality is realiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…In contrast to the drying in air, preheating treatment in steam was found to be beneficial for the DCL of coals [45]. Preheating treatment of coal in sub-critical steam at 385 °C (by rapid heating) for 15 min increased the oil yield in the subsequent liquefaction of the coal from 12.5% for the raw coal to 29% for the steam-treated coal [45]. Again, the stream pretreated coal must be prevented from exposure to air, as the exposure would decrease the oil yield and the liquefaction conversion to almost the same levels as those of the un-treated coal.…”
Section: Thermal and Hydro-thermal Treatmentmentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast to the drying in air, preheating treatment in steam was found to be beneficial for the DCL of coals [45]. Preheating treatment of coal in sub-critical steam at 385 °C (by rapid heating) for 15 min increased the oil yield in the subsequent liquefaction of the coal from 12.5% for the raw coal to 29% for the steam-treated coal [45]. Again, the stream pretreated coal must be prevented from exposure to air, as the exposure would decrease the oil yield and the liquefaction conversion to almost the same levels as those of the un-treated coal.…”
Section: Thermal and Hydro-thermal Treatmentmentioning
confidence: 85%
“…Moreover, retrogressive reactions responsible for coke formation would be favored when a coal is oxidized during drying in air, so it is desirable to dry the coal in vacuum or under an inert atmosphere and a lower temperature. In contrast to the drying in air, preheating treatment in steam was found to be beneficial for the DCL of coals [45]. Preheating treatment of coal in sub-critical steam at 385 °C (by rapid heating) for 15 min increased the oil yield in the subsequent liquefaction of the coal from 12.5% for the raw coal to 29% for the steam-treated coal [45].…”
Section: Thermal and Hydro-thermal Treatmentmentioning
confidence: 95%
“…141 The benefits of steam pretreatment can be realized only if the pretreated coal is then rapidly heated to liquefaction temperature. This is necessary, so that the pretreated coal can pass quickly through the temperature region where retrogressive effects occur.…”
Section: Nonradical Reactionsmentioning
confidence: 99%
“…Bienkowski et al found that the conversion of toluene solubles of Wyodak coal in liquefaction at 400 C increased from 27.3 to 38.4% by steam treatment at 200 C. 140 Ivanenko et al showed steam pretreatment substantially improves the quality of liquid product in coal slurry liquefaction and the oil yield is doubled under low severity conditions. 141 The benefits of steam pretreatment can be realized only if the pretreated coal is then rapidly heated to liquefaction temperature. This is necessary, so that the pretreated coal can pass quickly through the temperature region where retrogressive effects occur.…”
Section: Nonradical Reactionsmentioning
confidence: 99%
“…Moreover, hydrothermal treatment not only promotes the hydro-liquefaction activity in coal liquefaction [24,25] but also increases the coal concentration of coalsolvent slurry [26], then, the oil production cost of liquefaction process is reduced. Shui [27,28] has studied the effect of hydrothermal treatment on modifying caking and coking properties of the sub-bituminous coal.…”
Section: Introductionmentioning
confidence: 99%